Disruption of the 11-cis-Retinol Dehydrogenase Gene Leads to Accumulation of cis-Retinols and cis-Retinyl Esters - Driessen, Carola A. G. G. (American Society for Microbiology, 2000)
To elucidate the possible role of 11-cis-retinol dehydrogenase in the visual cycle and/or 9-cis-retinoic acid biosynthesis, we generated mice carrying a targeted disruption of the 11-cis-retinol dehydrogenase gene. Homozygous 11-cis-retinol dehydrogenase mutants developed normally, including their retinas. There was no appreciable loss of photoreceptors. Recently, mutations in the 11-cis-retinol dehydrogenase gene in humans have been associated with fundus albipunctatus. In 11-cis-retinol dehydrogenase knockout mice, the appearance of the fundus was normal and punctata typical of this human hereditary ocular disease were not present. A second typical symptom associated with this disease is delayed dark adaptation. Homozygous 11-cis-retinol dehydrogenase mutants showed normal rod and cone responses. 11-cis-Retinol dehydrogenase knockout mice were capable of dark adaptation. At bleaching levels under which patients suffering from fundus albipunctatus could be detected unequivocally, 11-cis-retinol dehydrogenase knockout animals displayed normal dark adaptation kinetics. However, at high bleaching levels, delayed dark adaptation in 11-cis-retinol dehydrogenase knockout mice was noticed. Reduced 11-cis-retinol oxidation capacity resulted in 11-cis-retinol/13-cis-retinol and 11-cis-retinyl/13-cis-retinyl ester accumulation. Compared with wild-type mice, a large increase in the 11-cis-retinyl ester concentration was noticed in 11-cis-retinol dehydrogenase knockout mice. In the murine retinal pigment epithelium, there has to be an additional mechanism for the biosynthesis of 11-cis-retinal which partially compensates for the loss of the 11-cis-retinol dehydrogenase activity. 11-cis-Retinyl ester formation is an important part of this adaptation process. Functional consequences of the loss of 11-cis-retinol dehydrogenase activity illustrate important differences in the compensation mechanisms between mice and humans. We furthermore demonstrate that upon 11-cis-retinol accumulation, the 13-cis-retinol concentration also increases. This retinoid is inapplicable to the visual processes, and we therefore speculate that it could be an important catabolic metabolite and its biosynthesis could be part of a process involved in regulating 11-cis-retinol concentrations within the retinal pigment epithelium of 11-cis-retinol dehydrogenase knockout mice.